The genomic architecture and molecular evolution of ant odorant receptors - McKenzie, Sean K.; Kronauer, Daniel J.C. (Genome Research, 2018)
The massive expansions of odorant receptor (OR) genes in ant genomes are notable examples of rapid genome evolution and adaptive gene duplication. However, the molecular mechanisms leading to gene family expansion remain poorly understood, partly because available ant genomes are fragmentary. Here, we present a highly contiguous, chromosome-level assembly of the clonal raider ant genome, revealing the largest known OR repertoire in an insect. While most ant ORs originate via local tandem duplication, we also observe several cases of dispersed duplication followed by tandem duplication in the most rapidly evolving OR clades. We found that areas of unusually high transposable element density (TE islands) were depauperate in ORs in the clonal raider ant, and found no evidence for retrotransposition of ORs. However, OR loci were enriched for transposons relative to the genome as a whole, potentially facilitating tandem duplication by unequal crossing over. We also found that ant OR genes are highly AT-rich compared to other genes. In contrast, in flies, OR genes are dispersed and largely isolated within the genome, and we find that fly ORs are not AT-rich. The genomic architecture and composition of ant ORs thus show convergence with the unrelated vertebrate ORs rather than the related fly ORs. This might be related to the greater gene numbers and/or potential similarities in gene regulation between ants and vertebrates as compared to flies.
10.1101/gr.237123.118